Ozone flux measurements over a Scots pine forest using eddy covariance method: performance evaluation and comparison with flux-profile method - Keronen, P.; Reissell, A.; Rannik, Ü.; Pohja, T.; Siivola, E.; Hiltunen, V.; Hari, P.; Kulmala, M.; Vesala, T. (Boreal Environment Research Publishing Board, 2024)
Ozone fluxes were measured over a forest in southern Finland between August 2001 and July 2002 using the eddy covariance method. Systematic errors due to the imperfect frequency response of the instrumentation and random errors due to the stochastic nature of turbulence were estimated. Flux underestimation correction factors for unstable stratification were 1.03–1.19. Random errors of the flux estimates were most frequently about 20% of the flux value. Fluxes were highest during the summer, declining to near zero during the winter. In summer, fluxes were higher during daytime than at night coinciding with higher turbulence and higher rate of stomatal uptake. Maximum summertime deposition velocities were 6–7 mm s–1. During winter, the diurnal pattern in ozone flux was weak and the deposition velocity was 0.5–1.5 mm s–1. Comparison between eddy covariance and profile flux measurement results generally showed good agreement during daytime.